Performance of nanoparticles as fluid loss additives in polymer-clay drilling fluids - Elisabet Sabu Hera, 1986-, author 558669 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2014